The micro-economics of export supply: Firm-level evidence from Mexico - Alfonso Cebreros (Banco de México, 2019)
This paper uses firm-level data for Mexican exporters to understand how firm-level export decisions shape a country's aggregate exports. The data allows for a characterization of both the crosssectional distribution of Mexican exports, across destinations and across exporting firms, and of the time-series variation in aggregate exports and its relation to time-series variation in the export supply decisions of firms. It is found that the cross-sectional variation of exports is mostly accounted for the extensive margins of trade, particularly the extensive margin of number of products exported, while the time-series variation in aggregate exports is mostly accounted for by the intensive margin of trade, and in particular by the growth of exporting firms that retain their export status from year to year.
Keywords: D21; F10; F12; F14; L1; L11; L21; L25; L60; 330; International trade; firm heterogeneity; productivity; multi-product firms; exporter dynamics